Kontekstualisasi Maqashid Shari’ah Dalam Sustainable Development Goals - Mohammad Farid Fad (Universitas Wahid Hasyim Semarang, 2019)
Abstract The process of building a nation will never be separated from relations with other nations in the world. But on the other hand, development often only emphasizes the aspect of growth, it forgets the most important element, namely equity. As a result, the poverty curve is not decreasing, but it remains a problem in itself to create gaping gaps. In order to respond to fundamental problems, the world responds by setting sustainable development goals that contain 17 points. Then how is the contextualization of the objectives of contemporary Islamic law in response to the mandate of the SDGs? The type of method used in this study is a qualitative method. After the data is collected, an analysis is performed using descriptive-analytical methods to get a critical interpretation of the SDGs picture in the perspective of maqashid shari'ah. Research shows that the Sustainable Development Goals, which are summarized in 17 points of The Global Goals, are very much in harmony with the principles of the objectives of contemporary Islamic law, namely the Maqashid shari'ah version of Jasser Auda.